Peningkatan Literasi Teknologi Guru Sekolah Dasar di Kecamatan Cijeruk Kabupaten Bogor - Stella Talitha; Suhendra; Rina Rosdiana; Sri Rahayu Dwiastuti; Muhamad Ginanjar Ganeswara (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
Pedagogy competency is teacher's ability to understanding of learners and learning management, from planning, implementing to evaluating. Pedagogical competencies to be improved in this activity is utilizing ICT for learning purposes. Technology-based learning media develops and enhances teachers' capabilities to fulfill their various roles and responsibilities related to becoming an educator. These technology-based learning media should provide teachers with wiggle room in the digital age to plan and provide interactive learning when participating in community or teacher work groups and practice in general with fellow educators. The target that has been achieved in community service activities in collaboration with Gugus Kecamatan Cijeruk in general is the increasing pedagogy of teachers in utilizing ICT for learning purposes. Specific targets that have been achieved in this activity include: (1) increasing teacher knowledge related to technology-based learning media, (2) increasing teacher technology literacy, (3) increasing the ability of teachers in making technology-based learning media. The method in this PkM, first establishing the target area and applying the appropriate permits for carrying out the activity to authorized institutions. Second, coordinating with Leader of Gugus Kecamatan Cijeruk and preparing training materials. The materials that have been provided, i.e. (1) introduction of technology literacy, (2) introduction and practice of basic ICT, dan (3) create learning media using ms. power point. In the training, methods the team uses are methods of lectures, demonstrations, discussions, and tasks.